Hungarian Monitoring, 28 January 1989 . [Magyar rádiófigyelő], 1989. január 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Press freedom in America, the USSR, West Germany, the GDR and Czechoslovakia - Yugoslav prime ministerial candidate's first program speech - Man who threatened self-immolation taken into custody in Prague - Polish workers' wage demands - Afghanistan's future after withdrawal of Soviet troops - Moscow organization plans memorial to victims of Stalinism Domestic Affairs: - Károly Grósz travels to Davos to give speech at European Community conference - Hungarian Socialist Workers' Party (MSZMP) Central Committee's Historical Sub-Committee re-evaluates 1956: 1956 was a popular uprising! - Parliament's Constitutional Committee recommendations: country should henceforth be called "Hungarian Republic"; probable referendum on new constitution, new coat of arms and role of the president of the republic - Church leaders and politicians take part in debate on religion at the Party's Political College - National Association of Hungarian Journalists (MÚOSZ) brings general assembly forward - Widow of Pál Maléter wants public reburial for her martyred husband Economy: - 9th meeting of young economists in Salgótarján - Beginning with February 9, banks will be allowed to decide on their interest rates themselves - OTP's monopoly in this field comes to an end - Village Radio:it was declared at the meeting of the Consumers' National Council the coops belong neither to the party, nor to the state Külpolitika: - Sajtónyilvánosság Amerikában, a SZU-ban, Nyugat-Németországban, az NDK-ban és Csehszlovákiában - A jugoszláv miniszterelnök jelölt első programbeszéde - Prágába őrizetbe vettek egy férfit, aki tűzhalállal fenyegetőzött - Lengyel dolgozók bérkövetelései - Afganisztán jövője a szovjet csapatok kivonulása után - Egy moszkvai szervezet emlékmű felállítását tervezi a sztálinizmus áldozatainak Belpolitika: - Grósz Károly Davosba utazott, hogy előadást tartson az Európai Közösség tanácskozásán - Az MSZMP KB történelmi albizottsága 1956 újraértékeléséről: 1956 népfelkelés volt! - "Magyar Köztársaság" legyen hazánk neve ezentúl. - Valószínűleg népszavazás dönt az új Alkotmányról, az új címerünkről és a köztársasági elnök szerepéről. - Ezek a Parlament Alkotmányozó Bizottságának javaslatai - Egyházi és politikai személyiségek részvételével ma vitafórumot tartottak a vallásról a párt Politikai Főiskoláján - A MÚOSZ előrehozott közgyűlése - MALÉTER Pál özvegye nyilvános újratemetést kíván rendezni mártír halált halt férjének Gazdaság: - Fiatal közgazdászok 9-ik, salgótarjáni találkozója - Február elsejétől a pénzintézetek maguk dönthetnek a konkrét kamatok nagyságáról - Megszűnik az OTP monopolhelyzete e téren - Falurádió: A szövetkezet nem a párté, államé - Hangzott el a Fogyasztók Országos Tanácsának ülésén